Antibiotic-induced gut dysbiosis and barrier disruption and the potential protective strategies. Issue 6 (26th March 2022) - Duan, Hui; Yu, Leilei; Tian, Fengwei; Zhai, Qixiao; Fan, Liuping; Chen, Wei
Abstract: The oral antibiotic therapies administered widely to people and animals can cause gut dysbiosis and barrier disruption inevitably. Increasing attention has been directed toward antibiotic-induced gut dysbiosis, which involves a loss of diversity, changes in the abundances of certain taxa and consequent effects on their metabolic capacity, and the spread of antibiotic-resistant bacterial strains. Treatment with beta-lactam, glycopeptide, and macrolide antibiotics is associated with the depletion of beneficial commensal bacteria in the genera Bifidobacterium and Lactobacillus . The gut microbiota is a reservoir for antibiotic resistance genes, the prevalence of which increases sharply after antibiotic ingestion. The intestinal barrier, which comprises secretory, physical, and immunological barriers, is also a target of antibiotics. Antibiotic induced changes in the gut microbiota composition could induce weakening of the gut barrier through changes in mucin, cytokine, and antimicrobial peptide production by intestinal epithelial cells. Reports have indicated that dietary interventions involving prebiotics, probiotics, omega-3 fatty acids, and butyrate supplementation, as well as fecal microbiota transplantation, can alleviate antibiotic-induced gut dysbiosis and barrier injuries. This review summarizes the characteristics of antibiotic-associated gut dysbiosis and barrier disruption, as well as the strategies for alleviating this condition. This information is intended to provide a foundation for the exploration of safer, more efficient, and affordable strategies to prevent or relieve antibiotic-induced gut injuries.